Deep and dark and dangerous - Hahn, Mary Downing (Boston : Sandpiper, 2007)
When thirteen-year-old Ali spends the summer with her aunt and cousin at the family's vacation home, she stumbles upon a secret that her mother and aunt have been hiding for over thirty years.
"Houghton Mifflin Harcourt."
Keywords: Cousins -- Juvenile fiction; Secrecy -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Ghost stories